Instituições participativas e as mudanças de governo: uma análise sobre democracia e cultura política participativa no governo de Jair Bolsonaro (2019-2022) - Silva, Beatriz Elena Barud (2023)
This thesis deals with actions of conservatism in Brazil, which saw, in 2019, the rise of an extreme right government, represented by Jair Bolsonaro (2019-2022), which in one of its first acts, eliminated and co-opted institutionalized forms of participation. Given this situation, we propose to investigate the following hypotheses: what is needed so that institutional participation does not suffer from alternations of power? We start from the understanding of institutional participation as that which develops in Participatory Institutions, institutional tools for political engagement that allow the exercise of citizenship, in addition to voting, thus strengthening the public arena and democracy. We use a qualitative methodology of bibliographic and documentary analysis, as well as data available on global platforms such as the World Values Survey. We began the research by revisiting notions about democracy and Brazilians' trust in Institutions and realized that distrust of government actions has been with us since the Proclamation of the Republic. After building a theoretical basis, we opened the documentary analysis of government decrees (2019-2022) that reduced participation and its impact on society. Finally, we carried out a case study in two National Public Policy Councils, the National Council for the Rights of Children and Adolescents – Conanda and the National Council to Combat Discrimination/LGBT, with the aim of strengthening the importance of such spaces in democratic constructions. The discussion about anti-democratic attitudes that weaken democracy is part of a broad research context, in this sense, we investigate elements of our cultural policy that are related to low participatory culture. In short, participation in Participatory Institutions needs to become an institutionalized State policy, less susceptible to dismantling and citizens need to be able to access and remain in these spaces, but we experience a society with fragile emotional and solidarity bonds